Not Just Scraping By: Experimental Evidence for Large Cutting Tools in the High Lodge Non-handaxe Industry - Stileman, Finn; Shipton, Ceri; Ashton, Nick (Springer Nature, 2024)
The presence or absence of handaxes endures as the major criterion of Lower Palaeolithic classification, with contemporaneous core-and-flake industries modelled as simpler counterparts to Acheulean technology. This is based on the supposed absence of formal tools, particularly of large cutting tools (LCTs) which are understood to be important within Acheulean lifeways, functioning as butchery knives among other uses. Scrapers from the core-and-flake industry of High Lodge (MIS 13) evidence formalised flake-tool production techniques, geared towards large tools with long cutting edges and acute angles, comparable in many respects to Acheulean handaxes. A holistic set of experiments was designed to test the production, efficiency, and practical utility of these scrapers. The experiments compared these scraper forms against handaxes and Quina scrapers. Their use in roe deer butchery indicates functional differences but demonstrates the appropriacy of both large, refined scrapers, and handaxes for processing carcasses of this size. The results support the inclusion of High Lodge scraper forms within the standard definition of LCTs. This interpretation challenges perceived discrepancies between handaxe and non-handaxe industries and deterministic explanations for Acheulean material culture. The feasibility of alternative LCTs supports the argument that the Acheulean represents socially inherited behaviours rather than latent reinventions.
Acknowledgements: We are grateful to the British Museum and staff at Franks House for facilitating access to study the High Lodge collection. We would also like to thank George Lazarus for kindly providing the deer carcasses and conducting the butchery experiments, Dr Alastair Key for providing the steel-frame apparatus for the clay and rope-cutting experiment, and to Dr Tomos Proffitt for creating the tools used in this pilot study. FS thanks Dr Matt Pope for supervising his undergraduate dissertation and Dr Andrea Zupancic for sharing his data from the Qesem Cave scrapers with us. NA thanks the Calleva Foundation for funding the Pathways to Ancient Britain project to which this paper is a contribution.
Keywords: 4301 Archaeology; 43 History, Heritage and Archaeology